133k views
11 votes
12x + 15y = 9
−12x − 18y = −6
HELP JUST SOLVE IT

User Bmo
by
6.9k points

2 Answers

3 votes
Solve for the first variable in one of the equations, then substitute the result into the other equation.
Point Form:
(2, -1)

Equation Form:
x= 2, y= -1
User Mu Mind
by
6.2k points
5 votes

Answer:

x = 2, y = -1

Explanation:

To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.

12x+15y=9,−12x−18y=−6

Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.

12x+15y=9

Subtract 15y from both sides of the equation.

12x=−15y+9

Divide both sides by 12.

x= 1/12 (−15y+9)

Multiply 1/12 ​ times −15y+9.

x = -5/4y+3/4

Substitute -5y+3/4 for x in te other equation, -12x - 18y = -6

-12 ( -5/4y+3/4) -18y = -6

Multiply −12 times -5y +3/4

15y−9−18y=−6

Add 15y to −18y.

−3y−9=−6

Add 9 to both sides of the equation.

−3y=3

Divide both sides by −3.

y=−1

Substitute −1 for y in x= -5/4y+3/4. Because the resulting equation contains only one variable, you can solve for x directly.

x= -5/4(-1)+3/4

Multiply -5/4 times -1.

x = 5+3/4

Add 3/4 to 5/4 by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.

x=2

The system is solved.

User Tikkanz
by
6.6k points